Promoting Classroom Interaction in English through Scaffolding Strategies, Meaningful Materials and Genres (2023)
ABSTRACT : This action-research aimed at promoting classroom interaction in English through scaffolding strategies, meaningful materials, and the genre of information report. It was conducted in a public school in Rionegro, Antioquia, with 35 ninth graders. Action research strategies unfolded in two stages: The first stage consisted of classroom observations to identify a research focus. During the second stage, an action plan was developed and implemented to address the limited of interaction in English in the classroom. Data gathering instruments included a multimodal pre-service teacher’s journal, focus group interviews, classroom recordings, and informal talks with students. Findings revealed a positive impact on classroom interaction in English in presence of teacher and peer scaffolding, blackboard-mediated interaction materials, and purposeful genre based planning.